The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12889-022-12951-1
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment strategies to promote uptake of cervical cancer screening in the West Region of Cameroon

Abstract: Objectives The World Health Organization’s (WHO) global strategy for cervical cancer elimination has set the target of 70% of women screened in all countries by 2030. Community sensitization through media is often used, but community health workers’ (CHW) involvement may contribute to improving screening coverage. We aimed to assess effectiveness and costs of two cervical cancer screening recruitment strategies conducted in a low-resource setting. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In this study, respondents also suggests that telemedicine can be used as effective tool in early detection of cancer by sharing pictures of cervix with consultants via digital cameras; was wellsupported with Arviliana and his co-associates 24 findings. Also, community information channels such as radio, television and advertisements raises cervical cancer awareness and engages large population in short period of time 25 ; well supports our findings i.e. cervical cancer screening programs must be advertised through mass media.…”
Section: Source Of Information With Respect To Cervical Cancer and It...supporting
confidence: 87%
“…In this study, respondents also suggests that telemedicine can be used as effective tool in early detection of cancer by sharing pictures of cervix with consultants via digital cameras; was wellsupported with Arviliana and his co-associates 24 findings. Also, community information channels such as radio, television and advertisements raises cervical cancer awareness and engages large population in short period of time 25 ; well supports our findings i.e. cervical cancer screening programs must be advertised through mass media.…”
Section: Source Of Information With Respect To Cervical Cancer and It...supporting
confidence: 87%
“…A cross-sectional, interventional study conducted in the Dschang health district observed a 30.1% (584/1940) increase in women’s attendance at the cervical cancer screening program following recruitment by community health workers (CHWs) [ 33 ]. These findings are similar to women’s participation in screening programs at 35.9% (1292/3600) in another study in where Community Mother and Child Aids (CoMCHAs) sensitized women about cervical cancer screening [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings are similar to women’s participation in screening programs at 35.9% (1292/3600) in another study in where Community Mother and Child Aids (CoMCHAs) sensitized women about cervical cancer screening [ 25 ]. Farmers and housewives, who are sometimes difficult to reach were more represented in the CHW-led recruitment at 42.6% and 25.2% [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations